Nghiên cứu chế tạo màng mỏng ZnO pha tạp Co bằng phương pháp Spin – Coating - Huỳnh, Lê Văn; Liên, Phạm Thị (Vietnam Journal of Chemistry, 2015)
Co-doped ZnO thin films are highly magnetic material is applied in the field of spintronics. This is a combination of microelectronics with the spin-related effects. The process of moving spins can carry information, easily spin control under the influence of an external magnetic field. This characteristic has been used in data storage technology using magnetism. Spin correlations and taking time to recover large, so it is likely to remain in the state for a long time. The advantage of this material is stable, large data transfer speed, low energy consumption, especially high integration capabilities than traditional semiconductor devices. In this paper, the research results are manufactured ​​Co-doped ZnO thin films by Spin-Coating method, with Co ≤ 12 % concentration does not change the crystal structure of ZnO. When the Co > 12 % concentration, it is no longer observed the crystallization of ZnO films anymore. The research results are the basis for the application of science to the practical production process technology.